2004
DOI: 10.1577/t03-058.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lowhead Dams on Riffle‐Dwelling Fishes and Macroinvertebrates in a Midwestern River

Abstract: Many studies have assessed the effects of large dams on fishes and macroinvertebrates, but few have examined the effects of lowhead dams. We sampled fishes, macroinvertebrates, habitat, and physicochemistry monthly from November 2000 to October 2001 at eight gravel bar sites centered around two lowhead dams on the Neosho River, Kansas. Sites included a reference site and a treatment site both upstream and downstream from each dam. Multivariate analysis of variance indicated that habitat, but not physicochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 33 publications
7
95
3
2
Order By: Relevance
“…However, our results showed that fish abundance and density of the sites immediately upper dams were lower than those of the two reference sites. This is similar with the pattern observed by Tiemann et al (2004), who revealed that low-head dams resulted in the significant decrease in fish abundance and density, not species richness, in the impoundment areas. Based on the linear regression analysis, we found the negative correlation between wetted width and fish abundance and density.…”
Section: Influences Of Low-head Dams On Fish Assemblagessupporting
confidence: 90%
See 4 more Smart Citations
“…However, our results showed that fish abundance and density of the sites immediately upper dams were lower than those of the two reference sites. This is similar with the pattern observed by Tiemann et al (2004), who revealed that low-head dams resulted in the significant decrease in fish abundance and density, not species richness, in the impoundment areas. Based on the linear regression analysis, we found the negative correlation between wetted width and fish abundance and density.…”
Section: Influences Of Low-head Dams On Fish Assemblagessupporting
confidence: 90%
“…Undoubtedly, the effects of low-head dams are smaller and more localized than those of large dams (Gillette et al 2005). By impoundment upstream, low-head dams alter the habitat characteristics in the stream segments immediately upstream of dams, such as the increase in channel width and water depth while the decrease in current velocity and substrate size (Dodd et al 2003;Tiemann et al 2004Tiemann et al , 2005Gillette et al 2005;Santucci et al 2005). In our results, the similar changes were observed for wetted with, water depth and current velocity, which was associated with the effects of the impoundment by low-head dams.…”
Section: Effects Of Low-head Dams On Local Habitatmentioning
confidence: 99%
See 3 more Smart Citations